2017
DOI: 10.1111/pre.12171
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic acclimation of Chlorella saccharophila to heat stress

Abstract: Photosynthesis is one of the most important metabolic processes of algae; which is altered as a stress response. During mass cultivation of algae, temperature rise and high light are major factors that affect biomass productivity. High temperature affects photosystem II (PSII) complex irreversibly, damaging intermolecular interactions in it. However, the impact of high temperature on photosynthesis is highly variable among different algal species, depending on the prior acclimation to environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Photosynthesis is one of the most important metabolic activities of algae, and chlorophyll is its main pigment. Studies have shown that when algae are stressed by the outside world, the algae cell chlorophyll a will also be affected(Alahverdi &Savabieasfahani 2012, Metzler et al 2018, Patil et al 2017. In this study, with the increase of the concentration of particulate matter, the chlorophyll a content of Microcystis os-aquae gradually decreased, that is, the higher the concentration of particulate matter, the stronger the attenuation of light by suspended particles.…”
Section: Effects Of Suspended Particles In Water On Lipid Peroxidatio...mentioning
confidence: 48%
“…Photosynthesis is one of the most important metabolic activities of algae, and chlorophyll is its main pigment. Studies have shown that when algae are stressed by the outside world, the algae cell chlorophyll a will also be affected(Alahverdi &Savabieasfahani 2012, Metzler et al 2018, Patil et al 2017. In this study, with the increase of the concentration of particulate matter, the chlorophyll a content of Microcystis os-aquae gradually decreased, that is, the higher the concentration of particulate matter, the stronger the attenuation of light by suspended particles.…”
Section: Effects Of Suspended Particles In Water On Lipid Peroxidatio...mentioning
confidence: 48%
“…Photosynthesis is one of the most important metabolic activities of algae, and chlorophyll is its main pigment. Studies have shown that when algae are stressed by the outside world, the algae cell chlorophyll a will also be affected (Alahverdi &Savabieasfahani 2012, Metzler et al 2018, Patil et al 2017. In this study, with the increase of the concentration of particulate matter, the chlorophyll a content of Microcystis os-aquae gradually decreased, that is, the higher the concentration of particulate matter, the stronger the attenuation of light by suspended particles.…”
Section: Effects Of Suspended Particles In Water On Lipid Peroxidation and Antioxidant Capacity Of Microcystis Osaquaementioning
confidence: 56%
“…It has been suggested that the stress-induced decrease in F v /F m is a short-term response of the photosystem under stress conditions, which may be a reconstructed equilibrium between light energy uptake and utilization by microalgae, minimizing damage to the algae [32]. Several studies have shown that the photosynthetic efficiency of algae decreases when subjected to environmental stress [33,34]. In this study, the F v /F m and F v /F o ratios of the algae decreased rapidly with increasing incubation time, indicating that the photosynthetic system of the microalgae was inhibited due to the addition of Zn 2+ .…”
Section: Chlorophyll Fluorescence Variables Of S Dohrnii Under Different Treatmentsmentioning
confidence: 99%